All-cause mortality risk associated with long-term exposure to ambient PM2·5 in China: a cohort study - Tiantian Li, ProfPhD; Yi Zhang, MPH; Jiaonan Wang, BSMed; Dandan Xu, BSMed; Zhaoxue Yin, MM; Huashuai Chen, PhD; Yuebin Lv, MM; Jiesi Luo, MM; Yi Zeng, ProfPhD; Yang Liu, PhD; Patrick L Kinney, ProfScD; Xiaoming Shi, ProfPhD (Elsevier, 2018)
Summary: Background: Evidence from cohort studies in North America and Europe indicates that long-term exposure to fine particulate matter (PM2·5) is associated with an increased mortality risk. However, this association has rarely been quantified at higher ambient concentrations. We estimated the hazard ratio (HR) for all-cause mortality from long-term exposure to PM2·5 in a well established Chinese cohort of older adults. Methods: The Chinese Longitudinal Healthy Longevity Survey (CLHLS) is a prospective cohort study of men and women aged 65 years and older enrolled in 2008 and followed up through 2014 for mortality events. We studied individuals for whom residential locations were available in 2008 for linkage to 1 km grids of PM2·5 concentrations, derived from satellite remote sensing. Cox proportional hazards models were used to estimate the effect of long-term exposure to PM2·5 on all-cause mortality, controlling for age, sex, smoking status, drinking status, physical activity, body-mass index, household income, marital status, and education. We then used our results to estimate premature mortality related to PM2·5 exposure in the population aged 65 years and older in China in 2010. Findings: 13 344 individuals in the CLHLS cohort had data for all timepoints, yielding follow-up data for 49 440 person-years. In a 3-year window, these individuals were exposed to a median PM2·5 concentration of 50·7 μg/m3 (range 6·7-113·3). The overall HR for a 10 μg/m3 increase in this value was 1·08 (95% CI 1·06-1·09). In stratified analyses, HRs were higher in rural than in urban locations, in southern versus northern regions, and with exposure to lower versus higher PM2·5 concentrations. Based on the overall HR, we estimated that 1 765 820 people aged 65 years and older in China in 2010 had premature mortality related to PM2·5 exposure. Interpretation: Long-term exposure to PM2·5 is associated with an increased risk of all-cause mortality among adults aged 65 years and older in China, but the magnitude of the risk declines as the concentration of PM2·5 increases. Funding: National Natural Science Foundation of China, National High-Level Talents Special Support Plan of China for Young Talents, US National Aeronautics and Space Administration, and the Columbia University Global Policy Initiative.